Research on the Reform of Teaching Computer Fundamentals in Art Majors under the Background of Integrating Ideology and Curriculum - He, Wenjing (Transactions on Social Science, Education and Humanities Research, 2024)
The goal of education is not only to cultivate knowledgeable and skilled individuals, but more importantly, to cultivate individuals with ethics, ideals, and the ability to succeed the socialist cause. Moral education should be integrated throughout the entire process of education and teaching, deeply integrated with various levels and disciplines, and guide students to establish correct worldviews, life values, and ideals, strengthen their sense of mission, and cultivate qualified socialist builders and successors. The concept of "integrating ideology and curriculum" aims to incorporate ideological and political education into teaching beyond the ideological and political classroom. Based on the characteristics of the curriculum itself, it integrates ideals and beliefs, national achievements, career ideals, excellent traditional culture, legal education, craftsmanship spirit, and labor education into curriculum teaching to achieve the goal of moral education. This article takes the university computer fundamentals course as the research object and explores the integration of ideology and curriculum in the teaching of computer fundamentals in art majors.